BOARD OF DIRECTORS' RESPONSIBILITY FOR DEBT RISK AT PT FIRMAN DIRGANTARA COI - Nurhalisa Amelia, Renni; Sulasno, Sulasno (NOMOI Law Review, 2025)
The responsibility of directors for risks arising from the management of accounts receivable and payable is a crucial aspect in maintaining the financial stability and reputation of the company. This study aims to determine the risks and legal responsibilities of directors for negligence or errors in the management of accounts receivable, using a case study of PT. Dirgantara Coi Word. The research method used was qualitative through an empirical legal approach. The results indicate that the responsibilities of directors are regulated by Law Number 40 of 2007 concerning Limited Liability Companies, specifically Articles 97 and 98, and are implementing other regulations. In PT. Firman Dirgantara Coi, it was found that late payments to creditors were caused by negligence in cash flow management and prudent decision-making, as well as bad debts from creditors. However, the directors demonstrated good faith and maintained professional relationships with business partners, so they were not personally liable.